A vermifiltration system for low methane emissions and high nutrient removal at a California dairy. (June 2022) - Dore, Sabina; Deverel, Steven J.; Christen, Nicholas
Abstract: Liquid storage of manure is a leading cause of methane emissions from the dairy sector and an important source of air and water pollution. This study monitored the effect of vermifiltration on methane emissions and water quality at a California dairy that uses an anaerobic lagoon. Methane fluxes and wastewater removal rate of volatile solids, N species, salinity, major ions, and trace elements were monitored for 12 months. Vermifiltration reduced methane emissions relative to an anaerobic lagoon by 97–99% and removed 87% of the volatile solids, contaminants such as salts and trace elements, P (83%) and N (84%) from the wastewater. Vermifiltration of dairy wastewater demonstrated to be a useful tool to mitigate methane emissions, regulate excess nutrients and improve water quality at dairy farms. Graphical abstract: Unlabelled Image Highlights: A vermifilter emitted 97% less CH4 than a dairy anaerobic lagoon. The vermifilter emitted 3.7 kg CH4 per cow per year. The vermifilter removed 87% of volatile solids from wastewater. The vermifilter removed 84% of N and 83% of P from wastewater.